2010
DOI: 10.1016/j.jtcvs.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of A1, A2A, or A3 adenosine receptors attenuates lung ischemia-reperfusion injury

Abstract: Objective Adenosine and the activation of specific adenosine receptors are implicated in the attenuation of inflammation and organ ischemia-reperfusion (IR) injury. We hypothesized that activation of A1, A2A, or A3 adenosine receptors would provide protection against lung IR injury. Methods Using an isolated, ventilated, blood-perfused rabbit lung model, lungs underwent 18 hours cold ischemia followed by 2 hours reperfusion. Lungs were administered either vehicle, adenosine, or selective A1, A2A, or A3 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 28 publications
2
53
0
Order By: Relevance
“…The cellular protection promoted by adenosine seems to be due to the activation of different subtypes of G proteins coupled receptors and its relationship of those with ATP dependent mitochondrial potassium channels, protein kinase C and mitogen activated protein kinase 15,16 . This idea is strengthened by the known effect of adenosine preconditioning, mediated by A 1 AR receptors, before organ ischemia, and this process has been described by the tolerance to injury arising from myocardial ischemia, in the early and late stages 13,14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular protection promoted by adenosine seems to be due to the activation of different subtypes of G proteins coupled receptors and its relationship of those with ATP dependent mitochondrial potassium channels, protein kinase C and mitogen activated protein kinase 15,16 . This idea is strengthened by the known effect of adenosine preconditioning, mediated by A 1 AR receptors, before organ ischemia, and this process has been described by the tolerance to injury arising from myocardial ischemia, in the early and late stages 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…In this way, drugs and cellular protector strategies to prevent or to attenuate systemic organ dysfunction must be investigated. Many types of strategies has been studied [5][6][7][8][9][10][11] , such as exogenous Adenosine treatment [12][13][14][15][16] and ischemic preconditioning [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for an anti-inflammatory role for A 1 R in lung 5 , liver 15 , kidney 16 , heart 17 , intestine 18 and skeletal muscle. 19 However, other studies have suggested that A 1 R antagonism has beneficial effects in lung and heart IR models.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, more recent studies, including our own, suggest that A 1 R activation has protective effects in several models of inflammatory lung injury. 5,11,12 Using A 1 R knockout mice and a specific pharmacological A 1 R agonist, the present study tests the hypothesis that specific A 1 R activation is anti-inflammatory and provides significant protection from lung IR injury.…”
Section: Introductionmentioning
confidence: 94%
“…Protective effects of adenosine receptor signaling classically occur through second messenger p a t h w a y s s u c h a s t h e c A M P / P K A o r p h o s pholipase C pathways. Most studies have provided evidence that A 1 R, A 2A R and A 3 R may primarily be involved in anti-inflammatory actions whereas the A 2B R may have more pro-inflammatory actions in the lung (Anvari, et al, 2010;Ellman, et al, 2008;Gazoni, et al, 2010;Reece, et al, 2005Reece, et al, , 2008Rivo, et al, 2004;Sharma, et al, 2009Sharma, et al, , 2010Sun, et al, 2006). However, the role of the A 2B R in IR injury remains less understood.…”
Section: Adenosine Receptorsmentioning
confidence: 99%